A Poetics of Place: Günter Kunert's Poem Sequence "Herbstanbruch in Arkadien" - Leonard Olschner (Studies in 20th & 21st Century Literature, 1997)
Kunert's volume of poetry Fremd daheim (Foreign at Home, 1990) defines a poetics of place, a poetics that demonstrates continuities in Kunert's lyric texts that reaches from his last years in the GDR, through his years in the old Federal Republic and beyond the Wende of 1989. Here he attempts to determine where the lyrical subject (or voice) is situated with respect to its origins and to trajectories into a future. Some poems thematize a return to the self as a homecoming, since no other homecoming is conceivable, while others commemorate travel and places abroad. The latter become metaphorical excursions into the self as well. The essay concentrates on the first sequence of the volume, "Herbstanbruch in Arkadien."
Keywords: Fremd daheim; Foreign at Home; Günter Kunerts; " Herbstanbruch in Arkadien" poetics of place; place; poetry; lyric texts; lyric; GDR; DDR; old Federal Republic; Wende; 1989; lyrical subject; voice; origins; future; return to self; homecoming; travel; abroad